Prevalence of Helicobacter pylori infection in newly arrived refugees attending the Migrant Health Service, South Australia. Issue 2 (22nd September 2016) - Abdul Rahim, Nur R.; Benson, Jill; Grocke, Kathryn; Vather, Deeva; Zimmerman, Jessica; Moody, Tessa; Mwanri, Lillian
Abstract: Background: To determine the prevalence of Helicobacter pylori infection in the refugee population attending the Migrant Health Service, South Australia, identify demographic factors associated with infection and compare prevalence of infection in refugees with that of the nonrefugee population in Australia. Materials and Methods: Cross‐sectional study conducted between October 2010 and August 2013. Monoclonal stool antigen testing for H. pylori infection is performed as part of a comprehensive health assessment for newly arrived refugees. The sample population included 922 adults and children. Outcome measures were (i) prevalence of H. pylori infection (ii) association between demographic factors such as sex, ethnicity and age, and H. pylori infection. Results: H. pylori infection was detected in 198 (21.5%) participants (95% CI 18.9%–24.3%). The odds of infection were lower in females OR 0.71 (95% CI 0.51–0.98) compared to males. Compared to Middle Eastern participants, the odds of infection were 1.75 (95% CI 1.17–2.62) times higher in African and 1.90 (95% CI 1.10–3.26) times higher in Burmese participants. Infection was not associated with age. Discussion and Conclusion: H. pylori infection is common among newly arrived refugees. The long latency of infection to development of complications and the availability of testing and relatively effective eradication regimens all add weight to a decision to screen in this population.